Deck the hounds [compact disc, unabridged] - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2018)
The Christmas season inspires Andy Carpenter to give some money to a homeless man, Don Carriganand, his dog Zooey. Shortly after Andy's encounter with them, Don and Zooey are attacked on the street in the middle of the night. When Andy's wife, Laurie learns that Andy had met the duo before, she sets them up with a home above Andy's garage. But it turns out that Don is wanted for a murder that happened two years ago. Don claims he's innocent and has no knowledge of the crime. Now it's up to Andy to exonerate his new friend.